Johnsonism and crisis management: a critical narrative analysis of the UK Prime Minister's response to the COVID-19 pandemic. - Bonnet, Alma-Pierre (Critical Discourse Studies, 2025)
As the official UK COVID Inquiry is investigating the response by the government to the 2020 global pandemic, revealing the difficulties that the Johnson administration had to face and the overall lack of adequate preparedness at the top of the UK executive, people are becoming growingly aware of the many challenges that such situations pose in terms of crisis management and public governance. Beyond the somewhat sterile blame game played by leading political actors, this formal accountability forum has also revealed competing narratives about the crisis that might have hampered any coherent political solution. This article proposes to focus on the 'official' narratives by the UK government and to analyse critically the way Boris Johnson narrativised his political response to the pandemic in order to examine how his unconventional style of leadership was deployed during a global crisis. Using a typology of crisis management inspired by crisis expert and leadership scholar Arjen Boin, the objective is to examine how 'crisis narratives' framed the way the UK government responded to the crisis.